2022
DOI: 10.1371/journal.pone.0270351
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 encapsulated in micelles ameliorates osteoarthritis by inhibiting inflammatory cell death

Abstract: Background Osteoarthritis (OA) is the most common degenerative joint disease and is characterized by breakdown of joint cartilage. Coenzyme Q10 (CoQ10) exerts diverse biological effects on bone and cartilage; observational studies have suggested that CoQ10 may slow OA progression and inflammation. However, any effect of CoQ10 on OA remains unclear. Here, we investigated the therapeutic utility of CoQ10-micelles. Methods Seven-week-old male Wistar rats were injected with monosodium iodoacetate (MIA) to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…It could also modulate the inflammatory pathways such as NF-κB and TLR, and control the release of pro-inflammatory cytokines in different disorders [ 167 , 168 ]. In this context, a recent in-vivo study has reported the effect of CoQ10-micelles as oral supplements in ameliorating the inflammation associated with OA [ 169 ]. Similar findings were also reported about melatonin, dihydromyricetin, quercetin, taurine, resveratrol and diallyl disulfide.…”
Section: The Inter-relation Between Various Metabolic Aspects In Oa R...mentioning
confidence: 99%
“…It could also modulate the inflammatory pathways such as NF-κB and TLR, and control the release of pro-inflammatory cytokines in different disorders [ 167 , 168 ]. In this context, a recent in-vivo study has reported the effect of CoQ10-micelles as oral supplements in ameliorating the inflammation associated with OA [ 169 ]. Similar findings were also reported about melatonin, dihydromyricetin, quercetin, taurine, resveratrol and diallyl disulfide.…”
Section: The Inter-relation Between Various Metabolic Aspects In Oa R...mentioning
confidence: 99%
“…Moreover, results from a study showed that CoQ10 could improve pain and cartilage degradation in MIA-induced OA rats [ 176 ]. In a more recent study, researchers encapsulated CoQ10 into micelles and found that CoQ10-micelles had a better chondroprotective effect than CoQ10 in OA rats [ 177 ]. Moreover, CoQ10-micelles could decrease the expression levels of catabolic and necroptotic factors in human OA chondrocytes [ 177 ].…”
Section: Antioxidantsmentioning
confidence: 99%
“…In a more recent study, researchers encapsulated CoQ10 into micelles and found that CoQ10-micelles had a better chondroprotective effect than CoQ10 in OA rats [ 177 ]. Moreover, CoQ10-micelles could decrease the expression levels of catabolic and necroptotic factors in human OA chondrocytes [ 177 ]. Another study also reported the anticatabolic and cartilage protective potential in rat chondrocytes [ 178 ].…”
Section: Antioxidantsmentioning
confidence: 99%
“…Additionally, specific nutraceuticals and dietary supplements have been investigated for their effects on mitochondrial metabolism in OA. Coenzyme Q10 (CoQ10), an essential component of the mitochondrial electron transport chain, has shown promise in improving mitochondrial function and reducing pain in OA patients [98,99]. Likewise, resveratrol, a polyphenol found in grapes and berries, has been studied for its antioxidant and anti-inflammatory properties, which may contribute to enhanced mitochondrial function in OA [100,101].…”
Section: Conclusion and Future Directionmentioning
confidence: 99%